1965
DOI: 10.1039/tf9656100037
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric powers and entropies of the hydrogen ion

Abstract: Initial and final (steady-state) thermoelectric powers have been determined for the strong acids HCl, H2S04, HClO4 and HNO3 at a series of concentrations by the use of quinhydrone electrodes at a mean temperature of 25°C. From these values have been determined entropies of transport and transported entropies as well as their concentration dependence. By extrapolation the standard transported entropy of the hydrogen ion has been determined as 5-1 cal/mole deg. Support for the results has been found in other dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1969
1969
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…According to the basic rules of irreversible processes thermodynamics,14 the initial and steady-state TEP of cell (1) [reaction (1)] are determined by the equations :…”
Section: Resultsmentioning
confidence: 99%
“…According to the basic rules of irreversible processes thermodynamics,14 the initial and steady-state TEP of cell (1) [reaction (1)] are determined by the equations :…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, however, we have found that electrode systems are quite stable and even for the ethanol concentration as high as 99.9% by weight, the eo value may be reproduced within _+ 7 ~V/deg and the E~ value to within ___ 5 ~V/deg. It is also interesting to note that no such difficulty was observed by Breck, Cadenhead, and Hammerli (6), where they have carried their thermocell measurements in aqueous solvent up to as high as 1.0N in HC1. The results of e~ measurements are shown in Table I.…”
Section: Methodsmentioning
confidence: 94%
“…Cell solutions were prepared by the method described by previous authors (6,8). The quinhydrone (Fisher reagent grade) was washed several times with the acid solution prior to its addition into the cell solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations